ANALYSIS OF THE MARKET OF SPORTS AND HEALTH ACTIVITIES AT MEZOROVNA - ROMANENKO, Serhii (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Today, sports and health activities are becoming one of the main trends in civilization, which have a systemic impact on the development of social relations, human development, and economic growth. Evidence of this is the annual increase in the population involved in various professional and mass sports, who dedicate part of their lives to active training and participate in mass sports, health events, and micro-enterprises. The article aims to analyze the market of sports and health activities at the meso level in Ukraine.The need for sports and health activities at the meso level in Ukraine is analyzed. The analysis showed that in the regional context, the largest volumes of services in the field of sports in 2020 were provided in Kyiv, Dnipropetrovsk, Kharkiv, Lviv, and Odesa regions, which is natural from the standpoint of the population in these regions. At the same time, the dynamics of the highest rates (increase by almost 3-6 times) of the sports services market for the period 2015-2020 are observed in Dnipropetrovsk (+ 619%), Kyiv (+ 670%), Vinnytsia (+ 369%), Zhytomyr (+ 361%), Donetsk (+ 455%), Ternopil (+ 398%) regions.It is proved that in Ukraine, despite the high level of human potential, professional sports development is in a state of stagnation. With insufficient financial support from the state and local authorities, sporting events become possible only with sponsorship; in most regions, there are no conditions for training (outdated infrastructure, high energy costs, low pay for coaches), and young people's choice is limited Regarding development in various sports, most of the existing sections provide only paid services, which reduces their accessibility for children and young people from low-income families. These factors, as well as several systemic problems in the development of professional sports due to destructive social and economic phenomena inherent in the development of socio-economic systems in Ukraine in recent years, have led to the loss of Ukraine's common position in the international sports arena and the deteriorating overall image of the country.
Keywords: market of sports and health-improving activity; volumes of rendered services; meso level